National Agricultural Market: Present Status, Challenges and Way Forward - Shalendra and M.S. Jairath (Ind. Jn. of Agri. Econ., 2016)
The National Agricultural Market is a virtual market envisaged to operate on an electronic trading portal but supported by physical markets at the backend. It has the potential to bring in transparency, competitiveness, efficiency and better participation of farmers by integrating wide range of functions and functionaries like farmers, commission agents, traders, electronic auction, clearing and settlement, payment gateway, logistics, warehousing, banking with facilities for grading and assaying. The concept is being implemented in India as a central sector scheme of the Ministry of Agriculture and Farmers Welfare with a target to network 585 markets over next three years. The concept may prove to be a game changer for Indian agriculture subject to adoption of more focused and balanced approach in participation of states and commodities, evolving detailed guidelines for service provides along with their roles, responsibility, charges and mechanism to address the disputes, development of a time bound strategy to educate different stakeholders on the importance and benefits available for them under NAM. Equally important will be to encourage states to undergo for reforms mainly in provisions considered vital for implementation of the national market. The implementation of the concept in the light of above suggestions along with a mechanism for monitoring, supervision and evaluation by the third party with no conflict of interest with the implementing agencies may help emerge the national agricultural market as a real game changer for Indian agriculture.